Teologi Trinitarian Calvin: Doktrin Autotheos Sebagai De Novo Dan Koreksi Untuk Konsili Nicea? - Mantiri, Lily Grace (STT Pelita Dunia, 2024)
Calvin's Trinitarian formulation, especially his view that the three Persons of the Trinity are autotheos, is considered unique, de novo. It even deviates or at least is a correction to the Nicene Creed (325 AD). Answering this problem, using a historical theology approach, this paper discusses Calvin's views on the doctrine of the Trinity. The author will show that Calvin's formulations of Trinitarian theology did not emerge from a vacuum but were expressed based on the theological struggles of his time. In other words, Calvin's view of the Triune God must be placed in its historical context. Through this research, the author underlines Calvin's widely recognized contribution, namely his assertion that the Father, Son, and Holy Spirit are three distinct persons but have one essence because they are autotheos. Calvin's concept of autotheos should be considered a clarifying contribution to the Nicene Creed.